Marlowe returns: da “Murder, My Sweet” a “Farewell, My Lovely” - Adriano Piccardi (Prof. Rinaldo Rinaldi, 2021)
Dick Richards’s “Farewell My Lovely” (1975) is a remake of – but not only – Edward Dmytryk’s film, “Murder, My Sweet” (1944). This essay explores the dialogue between Richards’s film and two texts, as well as between classical and modern cinema. In addition, it offers a close comparision between Richard’s film and its hypotext, Raymond Chandler’s novel, “Farewell My Lovely” (1940).